2018
DOI: 10.1080/07391102.2017.1415821
|View full text |Cite
|
Sign up to set email alerts
|

Combined pharmacophore, virtual screening and molecular dynamics studies to identify Bruton’s tyrosine kinase inhibitors

Abstract: Bruton's tyrosine Kinase (BTK) is a cytoplasmic, non-receptor tyrosine kinase expressed in hematopoietic cells. BTK plays a critical role in many cellular signalling pathways making it a potential target to treat autoimmune diseases and cancer. BTK signalling is important for the production of arthritis-associated antibodies, and inhibiting BTK will help the system to block the production of disease-associated antibodies. In this study, we have implemented ligand-based pharmacophore modelling and virtual scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The highest energy gap was observed in MFCD01312897 with the HOMO‐LUMO gap energy of ‐0.02517 eV and lowest gap energy was observed in NCI_41500 with the HOMO‐LUMO gap energy of ‐0.11703 eV. The best hits showed minimal HOMO‐LUMO gap with the average energy difference of ‐0.07 eV, signifying the chemical reactivity of these compounds …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest energy gap was observed in MFCD01312897 with the HOMO‐LUMO gap energy of ‐0.02517 eV and lowest gap energy was observed in NCI_41500 with the HOMO‐LUMO gap energy of ‐0.11703 eV. The best hits showed minimal HOMO‐LUMO gap with the average energy difference of ‐0.07 eV, signifying the chemical reactivity of these compounds …”
Section: Resultsmentioning
confidence: 99%
“…The best hits showed minimal HOMO-LUMO gap with the average energy difference of -0.07 eV, signifying the chemical reactivity of these compounds. 67,68 4.6 | Post-docking analysis of best "hits"…”
Section: Density Functional Theory Analysismentioning
confidence: 99%
“…The selected five complexes protein–ligand were subjected to 100 ns (nanoseconds) simulations of molecular dynamics (MD) under constant pressure and temperature conditions and the stability of the molecules can be understood with simulations of MD complexes ( Sakthivel and Habeeb, 2018 , Tanneeru et al, 2015 , Tanneeru and Guruprasad, 2013 , Wan et al, 2019 ). All the simulations of MD were conducted by using Gromacs 2018, Ubuntu-18.04 LTS Linux platform.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have shown that the pharmacophore model can be very useful to design new molecules with pharmacological activity. [34]. In this investigation, LigandScout software [14] was used to develop two pharmacophores from both compounds 3 and 4.…”
Section: Physicochemical Parameters Of Both Compounds 3 Andmentioning
confidence: 99%